(untitled) (Journal of Health, Population and Nutrition, 2011)
This case-control study was conducted in the Dhaka Hospital of ICDDR,B to identify the risk factors of mortality in severely-malnourished children hospitalized with diarrhoea. One hundred and three severelymalnourished children (weight-for-age <60% of median of the National Center for Health Statistics standard) who died during hospitalization were compared with another 103 severely-malnourished children who survived. These children were aged less than three years and admitted to the hospital during 1997. On admission, characteristics of the fatal cases and non-fatal controls were comparable, except for age. The median age of the cases and controls were six and eight months respectively (p=0.05). Patients with low pulse rate or imperceptible pulse had three times the odds of death compared to the control group (p<0.01). The presence of clinical septicaemia and clinical severe anaemia had 11.7 and 4.2 times the odds of death respectively (p<0.01). Patients with leukocytosis (>15,000/cm3) had 2.5 times the odds of death (p<0.01). Using logistic regression, clinical septicaemia [adjusted odds ratio (AOR)=8.8, confidence interval (CI) 3.7-21.1, p=0.01], hypothermia (AOR=3.5, CI 1.3-9.4, p<0.01), and bronchopneumonia (AOR=3.0, CI 1.2-7.3, p<0.01) were identified as the significant risk factors of mortality. Severely-malnourished children (n=129) with leukocytosis, imperceptible pulse, pneumonia, septicaemia, and hypothermia had a high risk of mortality. The identified risk factors can be used as a prognostic guide for patients with diarrhoea and severe malnutrition. Key words: Bronchopneumonia; Case-control studies; Child nutritional disorders; Diarrhoea; Hypoglycaemia; Leukocytosis; Marasmic-kwashiorkor; Mortality; Risk factors; Bangladesh DOI: http://dx.doi.org/10.3329/jhpn.v29i3.7870 J HEALTH POPUL NUTR 2011 Jun;29(3):229-235